تأثير تمرينات ثبات الجذع على بعض المتغيرات البدنية ومستوي الأداء الفني لسباحة الزحف على البطن - المتولي، دينا متولي أحمد (جامعة الأسكندرية - كلية التربية الرياضية للبنين بأبوقير, 2018)
هدفت الدراسة إلى التعرف على تأثير تمرينات ثبات الجذع على بعض المتغيرات البدنية ومستوى الأداء الفني لسباحة الزحف على البطن، وقد تم استخدام المنهج التجريبي على عينة عمدية من طالبات الفرقة الأولى بكلية التربية الرياضية جامعة المنصورة، وبلغت عينة البحث الأساسية (٢٦) طالبة تم تقسيمهن إلى مجموعتين تجريبية وضابطة قوام كل منهما (١٣) طالبة، حيث تم تطبيق تمرينات ثبات الجذع أثناء فترة الإعداد البدني الخاص ضمن برنامج تعليمي لسباحة الزحف على البطن لمدة (٨) أسابيع وتطبيق تمرينات ثبات الجذع مع المجموعة التجريبية بينما تم تطبيق التمرينات المتبعة وفق طريقة التعليم المعتادة مع المجموعة الضابطة، وبعد الانتهاء من تطبيق البرنامج تم إجراء القياسات البعدية للمجموعتين التجريبية والضابطة ومعالجة البيانات إحصائيا، وكانت أهم الاستنتاجات أن تمرينات ثبات الجذع أثرت إيجابيا علي المتغيرات البدنية ومستوى الأداء لسباحة الزحف على البطن للمجموعة التجريبية بصورة أفضل من المجموعة الضابطة والتي تم تطبيق التمرينات المتبعة عليها وفق الطريقة المتبعة في تعلم سباحة الزحف على البطن، وفى ضوء ما أسفرت عنه استنتاجات البحث توصى الباحثة بضرورة تطبيق تمرينات ثبات الجذع عند تعليم سباحة الزحف على البطن واستخدامها في برامج التعليم لأنواع السباحات الأخرى.
The study aimed to identify the effect of Core Stabilization Exercises On Some Physical Variables And Technical Performance Level Of The Front Crawl stroke , has been using the experimental method to deliberate sample of students of the band First Division, Faculty of Physical Education - Mansoura University, And it amounted to sample the core (26), a student, has been divided into experimental groups and the control group strength of each (13 students), which was applied the Core Stabilization Exercises during their physical preparation period within the educational program for front crawl swimming for a period of 8 weeks and apply Core Stabilization Exercises with while the experimental group was applied exercises followed according to the usual method of education with the control group , After the completion of the application of the program was conducted dimensional measurements of experimental and control groups, and process data statistically, the most important conclusions was that Core Stabilization Exercises have positively affected on the physical variables and technical performance of the front crawl swimming experimental group were better than the control group , which was applied exercises followed by the manner followed in learning to front crawl swimming , In view of the resulted from research findings researcher recommends the need for the application of the Core Stabilization Exercises when teaching front crawl swimming and used in education programs for other swimming stroks.
Keywords: القدرات البدنية -- الأداء الفني -- رياضة السباحة -- البرامج التعليمية